Implementasi Kebijakan Merdeka Belajar–Kampus Merdeka (Studi pada Fakultas Ilmu Sosial dan Hukum Universitas Negeri Makassar) - Andi Aco Agus; Nur Asiah (Universitas Tadulako, 2021)
This study aims to determine the jurisdiction policy, the implementation policy, and the obstacles faced in the implementation of the Independent Learning-Independence Campus in Makassar. Faculty of Social Sciences and Law, Makassar State University.The type of research used is empirical legal research, namely sociological juridical (sociological jurisprudence) with the research approach used is a qualitative approach. Data collection techniques include: observation, interviews and documentation. The data obtained from the research results were processed using descriptive qualitative data analysis. The results of this study: The Jurisdiction of the MBKM Policy has been in line with the legal basis and objectives to provide decent and better education; Implementation of the MBKM Policy at FIS-H UNM has been going well. Obstacles to the Implementation of the MBKM Policy in FIS-H UNM, namely; Obstacles to Study Programs and lecturers are the need to readjust the curriculum, lack of human resources and internship partners as well as entrepreneurship, the lack of other study programs that run MBKM. Constraints experienced by students are less stable networks, less interactive learning processes, socialization that still needs to be done massive, especially in the study program, the slow input of grades, the lack of activities during the covid period.